About the reflective thought also known as the critical thinking - León, Federico R. (2014)
This article deals with the concept of reflective thought or critical thinking from its initial formulation as an intellectual attitude to its current articulation as a third level of cognitive processing. Issues dealt with include critical thinking as a goal, as a cognitive process, as a part of dual cognitive processes, as a measurable disposition, as a measurable ability and as an educational task.